Graphene oxide grafted polyethylenimine electron transport materials for highly efficient organic devices. Issue 44 (9th September 2015) - Kim, Jeongmo; Lee, Heeryung; Lee, Seung Joo; da Silva, Wilson Jose; bin Mohd Yusoff, Abd. Rashid; Jang, Jin
Abstract : We propose a mixture of graphene oxide and polyethylenimine ethoxylate as an efficient electron transport layer for organic solar cells. Abstract : We demonstrate that solution processed graphene oxide (GO) grafted polyethylenimine ethoxylate (PEIE) is an efficient electron transport layer for organic solar cells with an active layer that consists of poly(4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4- b ]thiophenediyl) (PTB7) mixed with [6, 6]-phenyl C71 butyric acid methyl ester (PC71 BM). The optimized GO:PEIE demonstrated the best efficiency of 8.21% compared to that of the GO and PEIE devices.